Direct and sensitive detection of dopamine using carbon quantum dots based refractive index surface plasmon resonance sensor - Eddin, Faten Bashar Kamal; Fen, Yap Wing; Muhamad Fauzi, Nurul Illya; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Omar, Nur Alia Sheh; Anuar, Muhammad Fahmi; Hashim, Hazwani Suhaila; Sadrolhosseini, Amir Reza; Abdullah, Huda (MDPI, 2022)
Abnormality of dopamine (DA), a vital neurotransmitter in the brain’s neuronal pathways, causes several neurological diseases. Rapid and sensitive sensors for DA detection are required for early diagnosis of such disorders. Herein, a carbon quantum dot (CQD)-based refractive index surface plasmon resonance (SPR) sensor was designed. The sensor performance was evaluated for various concentrations of DA. Increasing DA levels yielded blue-shifted SPR dips. The experimental findings revealed an excellent sensitivity response of 0.138◦/pM in a linear range from 0.001 to 100 pM and a high binding affinity of 6.234 TM−1. The effects of varied concentrations of DA on the optical characteristics of CQD thin film were further proved theoretically. Increased DA levels decreased the thickness and real part of the refractive index of CQD film, according to fitting results. Furthermore, the observed reduction in surface roughness using AFM demonstrated that DA was bound to the sensor layer. This, in turn, explained the blue shift in SPR reflectance curves. This optical sensor offers great potential as a trustworthy solution for direct measurement due to its simple construction, high sensitivity, and other sensing features.